Katalog rubrycel i schematyzmów zakonów męskich i żeńskich z obszaru historycznych ziem Rzeczypospolitej za lata 1690-2008 w zbiorze Biblioteki Uniwersyteckiej Katolickiego Uniwersytetu Lubelskiego Jana Pawła II - Chomentowska, Edyta (Archiwa, Biblioteki i Muzea Kościelne, 2021)
Repeatedly raised demands for the need to draw up the lists of directories (liturgical calendars) and schematisms became an incentive to produce a catalogue of directories and schematisms of male and female religious orders existing in the territory of the Polish Republic. This work is based on part of a collection of these kinds of printed documents stored in the University Library KUL and covering the years 1690-2008. Its size is estimated to be around 600 titles, which places it among the largest collections of this type in academic libraries in Poland. The entire bibliographic material was divided into two parts, the first of which includes male religious orders and congregations and the other female religious orders and congregations. Titles are listed chronologically according to administrative units which were part of various religious orders. A short description of religious orders includes mainly administrative divisions, which facilitates the identification of individual printed documents. The Catalogue ... was preceded by an introduction, in which attempts were made to introduce general characteristics of the presented part of the collection: its internal structure, size, and various elements of bibliographic description.